2016
DOI: 10.1108/afr-11-2015-0050
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and impact of index-insurance and credit for smallholder farmers in developing countries

Abstract: Purpose – The purpose of this paper is to review the most recent scientific literature on the determinants explaining the demand for index-insurance, the impact of index-insurance and the existing links between insurance and credit. In this meta-analysis, the authors identify key discoveries on the potential of index-insurance in enhancing credit supply for smallholders and thus farm productivity. Design/methodology/approach – Following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 54 publications
4
54
0
1
Order By: Relevance
“…Stewart et al (2012) attempted to include microinsurance in their review, but found the insurance services to be too recent to have an adequate evidence base. We found five meta-studies on insurance, including ones focused on on the effectiveness of index-based weather insurance Marr et al, 2016), and of micro health insurance (Bhageerati et al, 2017;Habib, Perveen, & Khuwaja, 2016;). However, all five were ranked low confidence during the assessment of methodological quality and risk of bias.…”
Section: Overall Completeness and Applicability Of Evidencementioning
confidence: 99%
“…Stewart et al (2012) attempted to include microinsurance in their review, but found the insurance services to be too recent to have an adequate evidence base. We found five meta-studies on insurance, including ones focused on on the effectiveness of index-based weather insurance Marr et al, 2016), and of micro health insurance (Bhageerati et al, 2017;Habib, Perveen, & Khuwaja, 2016;). However, all five were ranked low confidence during the assessment of methodological quality and risk of bias.…”
Section: Overall Completeness and Applicability Of Evidencementioning
confidence: 99%
“…In this way we make two advances to the literature and practice in the design of WII and the application to climate risk financing. On this latter point, insurance linked or bundled credit products have been promoted by a number of scholars including Skees and Barnett (2006), Gine and Yang (2009), Carter et al (2011), Karlan et al (2011), Miranda and Gonzales-Vega (2011), Collier et al (2011), Shee and Turvey (2012), Shee et al (2015), Marr et al (2016), Pelka et al (2015), Carter et al (2016), von Negenborn et al (2018 and Mishra et al (2018). Clarke and Grenham (2013) and Jensen et al (2016) point out that basis risk limits farmers' investment in weather index insurance.…”
Section: − = −mentioning
confidence: 99%
“…Cole et al (2012) systematically reviewed the literature on agricultural index insurance but found no papers with evidence regarding the impacts on income, productivity, or food and nutrition security despite including these in the search. Marr et al (2016) systematically reviewed the literature on index insurance including takeup, impacts and interactions with credit products in developing countries. They identified only two papers, both with positive results, showing empirical evidence of the effect of index insurance on income/consumption, although they included papers that modelled both negative and positive effects on income.…”
Section: Improved Access To Financial Productsmentioning
confidence: 99%